Pemanfaatan Pekarangan Rumah untuk Mendukung Ketahanan Pangan dan Gizi Keluarga Petani di Desa Lolanan: Pemanfaatan Pekarangan Rumah untuk Mendukung Ketahanan Pangan dan Gizi Keluarga Petani di Desa Lolanan - Moh. Rizki Fauzan; Hairil Akbar; Carli Mamonto; Anindya Adelweis Kanahaya; Ni Nyoman Darmiasih; Ramadhanya Limo; Reva Nurshifa Kolopita (STIKES Yayasan RS.Dr.Soetomo, 2026)
Home gardens are an accessible and sustainable resource for improving household food security and family nutrition, particularly among farming communities. However, many households in Lolanan Village have not fully utilized their home gardens due to limited knowledge and skills in productive, environmentally friendly cultivation practices. This community service program aimed to enhance community knowledge and awareness of home garden utilization to support household food security and nutrition. A participatory action approach was implemented on October 1, 2024, involving farming families in Lolanan Village. The activities included interactive education, group discussions, and practical demonstrations on vegetable cultivation, vertical gardening, polybag planting, household organic compost production, and medicinal plant cultivation. Program evaluation was conducted through observation, oral questioning, and participant discussions. The program improved participants' knowledge and understanding of the benefits of home gardens, crop diversification, organic fertilizer use, and simple cultivation techniques suitable for limited land. Interactive learning methods encouraged active participation and increased participants' confidence in implementing sustainable gardening practices. Collaboration among community members, village authorities, lecturers, and students further supported the successful implementation of the program. Participatory education and community empowerment effectively strengthened community awareness of home garden utilization as a strategy to improve household food security and family nutrition. Continuous mentoring and collaboration with local stakeholders are recommended to sustain the program's long-term impact.